Analisis Perbedaan Kinerja Keuangan Sebelum dan Sesudah Kenaikan Harga Tiket pada PT. Garuda Indonesia (Persero) TBK - Khoir, Miftahul; Kesuma, Ali (Keizai, 2021)
This study aims to determine the differences in financial performance before and after the ticket price increase policy at PT. Garuda Indonesia (Persero) Tbk. in 2016-2019. The technique used in sampling is the purposive sample technique. This research was analyzed using the Du Pont System analysis tool. To test the differences in financial performance using Paired Sample T-test. where the test was carried out using the SPSS application program. The results of the study based on the Paired Sample T-test show that the total assets turnover has differences after the ticket price increase, while current ratio, return on assets, return on equity, return on investment, net profit margin, and debt to equity ratio have no difference after a ticket price increase.